A pupal transcriptomic screen identifies Ral as a target of store-operated calcium entry in Drosophila neurons - Richhariya, Shlesha (Sci Rep, 2017)
Transcriptional regulation by Store-operated Calcium Entry (SOCE) is well studied in non-excitable cells. However, the role of SOCE has been poorly documented in neuronal cells with more complicated calcium dynamics. Previous reports demonstrated a requirement for SOCE in neurons that regulate Drosophila flight bouts. We refine this requirement temporally to the early pupal stage and use RNA-sequencing to identify SOCE mediated gene expression changes in the developing Drosophila pupal nervous system. Down regulation of dStim, the endoplasmic reticular calcium sensor and a principal component of SOCE in the nervous system, altered the expression of 131 genes including Ral, a small GTPase. Disruption of Ral function in neurons impaired flight, whereas ectopic expression of Ral in SOCE-compromised neurons restored flight. Through live imaging of calcium transients from cultured pupal neurons, we confirmed that Ral does not participate in SOCE, but acts downstream of it. These results identify neuronal SOCE as a mechanism that regulates expression of specific genes during development of the pupal nervous system and emphasizes the relevance of SOCE-regulated gene expression to flight circuit maturation.